High-resolution FLAIR MRI at 7 Tesla for treatment planning in glioblastoma patients - Regnery, Sebastian; Windisch, Paul; Harrabi, Semi B.; Bernhardt, Denise; Ladd, Mark E.; Rieken, Stefan; Debus, Jürgen; Adeberg, Sebastian (Radiotherapy and oncology, 2019)
Ultra-high field MRI is an emerging technique promising high-resolution images for radiotherapy planning. We compared a 7 Tesla FLAIR sequence with clinical FLAIR imaging at 3 Tesla in glioblastoma patients before radiotherapy. High-resolution 7 Tesla FLAIR imaging may enhance the depiction of organs at risk and possibly modify target volumes.
Available online 31 August 2018
Gesehen am 05.07.2019